Pengaruh Latihan Sepakbola Empat Gawang Terhadap Kemampuan Passing Stopping Sepakbola Ekstrakurikuler di SMP Islam Karawang - NurIlham Muhammad Sidik; Febi Kurniawan; Rustam Effendi (Universitas Singaperbangsa, 2021)
This research is motivated by the lack of variations in the practice of playing football, thus causing saturation for learners. In addition, the ability of learners in doing passing-stopping is still not good. This study aims to determine the significant effect of four-wicket football practice on basic passing-stopping footballing skills of SMP ISLAMIC KARAWANG Junior High School students. Research is an experimental research. The method used is one-group pretest-posttest design. The population of this study were students of SMP ISLAMIC KARAWANG class VIII, which amounted to 16 children. Sampling technique is random sampling. The instrument used is a passing-stopping skill test with bounce board. The analysis technique used is by using t-test analysis. The results of this study indicate that there is significant influence of four-wicket football practice on the basic passing-stopping footballing ability of playing football of students of class VIII SMP ISLAMIC KARAWANG. When viewed from the Mean Difference number of2.625 and the pretest average of 15.31, this shows that the exercise performed can give a better change of 17.14% for the ability of passing-stopping the ball than before the exercise.